2014
DOI: 10.1007/s00253-014-6208-3
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of ethyl mercaptan and its major intermediate diethyl disulfide by Pseudomonas sp. strain WL2

Abstract: A Pseudomonas sp. strain WL2 that is able to efficiently metabolize ethyl mercaptan (EM) into diethyl disulfide (DEDS) through enzymatic oxidation was isolated from the activated sludge of a pharmaceutical wastewater plant. One hundred percent removal of 113.5 mg L(-1) EM and 110.3 mg L(-1) DEDS were obtained within 14 and 32 h, respectively. A putative EM degradation pathway that involved the catabolism via DEDS was proposed, which indicated DEDS were further mineralized into carbon dioxide (CO2), bacterial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Pseudomonas aeruginosa BM-B-450, which was isolated from an n -pentane-adapted consortium, can degrade MTBE [25]. Members of the Pseudomonas genus have found innumerous environmental niches on Earth and have demonstrated the ability to mineralize various pollutants, including polycyclic aromatic hydrocarbons (PAHs) [26,27], benzene [28], and alcohols [29,30]. Strains from the Pseudomonas genus meet the requirements for industrial biotechnology, including high biomass production and low nutritional demands.…”
Section: Resultsmentioning
confidence: 99%
“…Pseudomonas aeruginosa BM-B-450, which was isolated from an n -pentane-adapted consortium, can degrade MTBE [25]. Members of the Pseudomonas genus have found innumerous environmental niches on Earth and have demonstrated the ability to mineralize various pollutants, including polycyclic aromatic hydrocarbons (PAHs) [26,27], benzene [28], and alcohols [29,30]. Strains from the Pseudomonas genus meet the requirements for industrial biotechnology, including high biomass production and low nutritional demands.…”
Section: Resultsmentioning
confidence: 99%
“…According to previous reports, members of the Pseudomonas genus have been found in numerous environmental niches on Earth and have demonstrated the ability to mineralize various pollutants, such as polycyclic aromatic hydrocarbon (PAH) [ 19 , 20 ], benzene [ 21 ], alcohols [ 22 , 23 ], etc. The various desirable characteristics of Pseudomonas genus strains make them meet the requirements of industrial biotechnology, including higher biomass productions and lower nutritional demands.…”
Section: Resultsmentioning
confidence: 99%
“…The biodegradation pathway of EM and DMDS has not been well deciphered in literature. A few reports found that the EM degradation was initiated by formation of diethyl disulfide [21, 22]. Although the main end products were confirmed as elemental sulfur and sulfate based on the calculation of sulfur mass balance, the subsequent oxidation route of diethyl disulfide remains unclear, and enzymes and genes involved were not reported.…”
Section: Discussionmentioning
confidence: 99%